2011
DOI: 10.1002/ijc.26290
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Galectin‐1 in pancreatic stellate cells plays a role in the development and maintenance of an immunosuppressive microenvironment in pancreatic cancer

Abstract: Galectin-1 is implicated in making tumor cells immune privileged, in part by regulating the survival of infiltrating T cells. Galectin-1 is strongly expressed in activated pancreatic stellate cells (PSCs); however, whether this is linked to tumor cell immune escape in pancreatic cancer is unknown. Galectin-1 was knocked down in PSCs isolated from pancreatic tissues using small interfering RNA (siRNA), or overexpressed using recombinant lentiviruses, and the PSCs were cocultured with T cells. CD31 , CD4 1 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
139
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(156 citation statements)
references
References 50 publications
(70 reference statements)
1
139
0
1
Order By: Relevance
“…Research from our laboratory has recognized an essential role for Gal1 as an immunoevasive mechanism in human and mouse melanoma (9). These observations were further confirmed in mouse lung adenocarcinoma (10,11), and in human cancers including Hodgkin lymphoma (12,13), neuroblastoma (14), head and neck squamous cell carcinoma (15), pancreatic carcinoma (16), glioma (17), and T-cell lymphoma (18), suggesting that targeting the Gal1-glycan axis might contribute to overcome immunosuppression and potentiate immunotherapeutic approaches. Interestingly, Gal1 was identified as a tumor-associated protein capable of delineating the metastatic potential of human breast carcinoma (19,20).…”
Section: Introductionmentioning
confidence: 58%
“…Research from our laboratory has recognized an essential role for Gal1 as an immunoevasive mechanism in human and mouse melanoma (9). These observations were further confirmed in mouse lung adenocarcinoma (10,11), and in human cancers including Hodgkin lymphoma (12,13), neuroblastoma (14), head and neck squamous cell carcinoma (15), pancreatic carcinoma (16), glioma (17), and T-cell lymphoma (18), suggesting that targeting the Gal1-glycan axis might contribute to overcome immunosuppression and potentiate immunotherapeutic approaches. Interestingly, Gal1 was identified as a tumor-associated protein capable of delineating the metastatic potential of human breast carcinoma (19,20).…”
Section: Introductionmentioning
confidence: 58%
“…Another PDAC-associated adhesion molecule, an ICAM-1 receptor α L β 2 integrin (also known as LFA-1 or CD11a/CD18), regulates CD8 + T cell recruitment: only its knockout results in a marked impairment of CD8 + T cell infiltration in experimental pancreatic tumors in mice, probably because its lack of expression impairs T cells activation and differentiation [112]. Overexpression and secretion by activated PSCs of β-galactoside-binding protein Galectin-1 (Gal-1), another molecule that mediates immunosuppression in PDAC by targeting T cell, increases Th2 and decreases Th1 cytokines, inducing CD4 + and CD8 + T cell apoptosis [113].…”
Section: Immune Effector Cellsmentioning
confidence: 99%
“…Genetic ablation of Gal-1 in a murine PDAC model dampened tumor progression by inhibiting proliferation, angiogenesis and the desmoplasic reaction, and also by triggering a tumor-associated immune response, thus leading toa 20% increase in relative lifespan [145]. However, Gal-1 overexpression is found on the stromal tissues of long term pancreatic cancer survivors [113], indicating that the prognostic significance of Gal-1 expression is not entirely clear. Blocking molecules for Gal-1 is a potential strategy for cancer treatment.…”
Section: Changes In Tumor-associated Antigens (Taas)mentioning
confidence: 99%
“…In vitro experiments have shown that Gal1 is involved in pancreatic stellate cell activation [10,11] , contributing to the immune escape [12] and favoring tumor invasion and migration [13,14] . Although in humans, Gal1 tumor levels faithfully correlate with PDA stage [15] and patient survival [16,17] , previous studies were only descriptive and did not provide any insights about the mechanism of the in vivo Gal1 role during pancreatic tumor progression.…”
Section: Research Highlightmentioning
confidence: 99%